2004
DOI: 10.1159/000081053
|View full text |Cite
|
Sign up to set email alerts
|

Brain Abscess: A Need to Screen for Pulmonary Arteriovenous Malformations

Abstract: Background: Pulmonary arteriovenous malformations (PAVMs) are direct connections between an artery and a vein in the pulmonary circulation associated with hereditary hemorrhagic telangiectasia in up to 88% of cases. Patients with PAVMs are at increased risk of brain abscess (BA). This study aimed to provide preliminary data on the prevalence of PAVMs among BA patients. Methods: Administrative hospital discharge forms were used to identify patients with BA; possible PAVM patients were screened. Results: 126 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…None of the HHT2 patients with large PAVMs had experienced neurological sequelae, but neurological complications secondary to PAVMs have been reported in HHT2 patients in literature, though to a lesser extent than that observed in HHT1 [19,24]. As neurological complications mainly occur in PAVMs with a feeding artery > 3 mm [22,25], few HHT2 patients are expected to suffer from brain involvement secondary to PAVMs. It is noteworthy that 6/12 HHT1 patients with PAVM‐related neurological complications were younger than 45 years; moreover, 11 HHT1 and only two HHT2 patients with large PAVMs were observed at an age < 45 years, suggesting that not only large PAVMs are more frequent in HHT1, but they are also rare in young HHT2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…None of the HHT2 patients with large PAVMs had experienced neurological sequelae, but neurological complications secondary to PAVMs have been reported in HHT2 patients in literature, though to a lesser extent than that observed in HHT1 [19,24]. As neurological complications mainly occur in PAVMs with a feeding artery > 3 mm [22,25], few HHT2 patients are expected to suffer from brain involvement secondary to PAVMs. It is noteworthy that 6/12 HHT1 patients with PAVM‐related neurological complications were younger than 45 years; moreover, 11 HHT1 and only two HHT2 patients with large PAVMs were observed at an age < 45 years, suggesting that not only large PAVMs are more frequent in HHT1, but they are also rare in young HHT2 patients.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that the risk is mostly influenced by the severity of the right-to-left shunting. The presence of PAVMs may not be recognized at the time of the brain abscess [18, 85, 86], which may develop in patients with diagnosed but untreated PAVMs [18]. Cerebral abscesses in HHT are frequently due to multiple anaerobic organisms [83] and predominate in supratentorial areas of the brain [80].…”
Section: Clinical Manifestations and Complications Of Pavmsmentioning
confidence: 99%
“…Clinically, an association between HHT and infectious diseases has been reported. Numerous cases indicated that particularly patients with HHT and pulmonary vascular malformations (PAVMs) or prolonged nasal packings for epistaxis are more susceptible to infections, cerebral abscesses, or septic thrombi [7][8][9][10][11]. A few studies reported life-threatening extracerebral severe infections, including osteoarthritis, septicemia, and spondylodiscitis, typically due to Staphylococcus aureus infection [12,13].…”
Section: Introductionmentioning
confidence: 99%